(untitled) (Open International Journal of Informatics, 2025)
The integration of the Internet of Things (IoT) devices in the healthcare system has enhanced patient care through remote monitoring, wearable devices, smart medical systems, and other embedded systems that track patients’ health. These advancements have boosted operational efficiency, cut costs, enabled real-time patient monitoring, and improved patient outcomes. However, the widespread adoption of IoT in healthcare also introduces significant privacy risks and vulnerabilities, exposing sensitive patient data to unauthorized access and breaches. This study aims to explore the threat related to the data breaches associated with healthcare IoT systems, review existing mitigation strategies, and propose future research directions to address these challenges. Using a literature review of publications published from 2019 to 2024, consisting of 25 articles selected, the keyword-related study is identified. The study examines IoT applications such as remote patient monitoring (RPM), wearable devices, and telemedicine, highlighting their role in improving patient outcomes while underscoring the associated risks of data exposure. Advanced solutions, including blockchain technology, federated learning, and AI-driven threat detection, were identified and evaluated as potential mitigation strategies. Findings reveal that IoT-enabled healthcare systems face persistent challenges, including a lack of standardized security protocols, resource constraints in IoT devices, and the complexity of maintaining data privacy across interconnected networks. By addressing current gaps and implementing advanced solutions, IoT devices can significantly enhance healthcare delivery without compromising patient privacy and data security.